2023
DOI: 10.1007/s10584-023-03495-3
|View full text |Cite
|
Sign up to set email alerts
|

Amplified drought trends in Nepal increase the potential for Himalayan wildfires

Abstract: In spring 2021, Nepal underwent a record wildfire season in which active fires were detected at a rate 10 times greater than the 2002-2020 average. Prior to these major wildfire events, the country experienced a prolonged precipitation deficit and extreme drought during the post-monsoon period (starting in October 2020). An analysis using observational, reanalysis, and climate model ensemble data indicates that both climate variability and climate changeinduced severe drought conditions were at play. Further a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Furthermore, we observed that 2016 and 2021 recorded the highest number of fire incidents, this observation aligns with findings of Parajuli et al [ 29 ] in Terai arc landscape of Nepal. According to Pokharel et al [ 95 ], extreme drought conditions and precipitation deficit were the likely reason for triggering the record breaking 2021 wildfire season. Additionally, we analysed the forest fire data to identify factors influencing fires in the Chure region using the GLM approach and created a forest fire susceptibility map.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed that 2016 and 2021 recorded the highest number of fire incidents, this observation aligns with findings of Parajuli et al [ 29 ] in Terai arc landscape of Nepal. According to Pokharel et al [ 95 ], extreme drought conditions and precipitation deficit were the likely reason for triggering the record breaking 2021 wildfire season. Additionally, we analysed the forest fire data to identify factors influencing fires in the Chure region using the GLM approach and created a forest fire susceptibility map.…”
Section: Discussionmentioning
confidence: 99%
“…The amount and frequency of precipitation, in conjunction with temperature, are commonly used to calculate fire severity indices (Van Wagner 1987, Flannigan andHarrington 1988). Precipitation during the fire season can influence wildfire activities either directly by wetting effects or indirectly through the feedback to soil moisture (Holden et al 2018, Sehler et al 2019, Pokharel et al 2023. The pronounced scarcity of summer rainfall and the rising temperature have emerged during the recent unprecedented Siberian wildfires (Zhu et al 2021, Descals et al 2022, Scholten et al 2022.…”
Section: Introductionmentioning
confidence: 99%
“…The wildfires of the last five years in Australia, Canada, the United States, Nepal, the Amazon, Siberia, and Europe have caused heavy loss of lives and property and the destruction of vast acres of land and forests with consequent implications for the success of the Sustainable Development Goals (SDGs) (Dye et al 2023;Pokharel et al 2023). Namely, the recent 2023 Hawaii wildfires have resulted in a tragic loss of a minimum of 96 individuals and incurred a staggering $5.52 billion in damages (Marris, 2023).…”
Section: Introductionmentioning
confidence: 99%